DINAMIKA PENGGUNAAN LAHAN DAN PARTISIPASI MASYARAKAT PADA HUTAN LINDUNG MUTIS TIMAU YANG DIKELOLA DENGAN POLA AGROFORESTRI (Studi Kasus di Desa Fatukoto dan Ius Molo, Kabupaten Timor Tengah Selatan) - , YAKUB BENU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mollo Utara regency is an area located around a protected forest and is the place where agroforestry is being practiced. The agroforestry pattern, with the passing of time, the dynamics and participation of society changes according dinamics.of agroforestry. This research is aimed at observing these agroforestry dynamics in Mutis Timau protected forest